MENUMBUHKAN NILAI KARAKTER SISWA MELALUI KEGIATAN SENI BARONGSAI KUDA TERBANG DI SD BAPTIS PALEMBANG - Anggiat Rio Murbowo (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The value of the regius and cultural characters in the art of the Flying Horse Barongs includes divine values, respect values, and life values that can be seen from symbolic forms. This study uses a qualitative method. This method seeks to explain how the value of character and cultural art of horse Trench Flying Palembang. The result of research on religious and cultural character values in the art of the horse dancing Barongsai is performed in the Baptist Elementary School. lions and some properties such as steel battles and a pair of big ropes, in addition to supporting the show there is lighting to make the show look more majestic, there is also music as a regulator of motion and attractions performed by Barongsai. The ritual value can be seen when the performance will be, where the Barongsai performs the prayer by doing the pies in front of the altar, given a splash of holy water and burning the hio made by the temperature or the trainer. The value of religious and cultural characters during the show can be seen when the Barongsai eat citrus leaves and then pay homage to the donors or the audience. The conclusion that the art of the horse lion dance has a religious and cultural value that contains divine values, respect values, and the value of life. Suggestions for the Flying Horse group to develop attractions such as Liong Kuda fly that spewed fire from his mouth in order to attract more people to watch.